Characterizing Cybersecurity Awareness Among Brazilian Computer Science Higher Education Students - Ferreira, Vinícius E.; OliveiraJr, Edson; Zarpelão, Bruno B.; Zorzo, Avelino F. (Anais do Workshop sobre Educação em Computação (WEI), 2025)
This study examines the cybersecurity awareness of Brazilian students at various academic levels, focusing on their understanding of fundamental concepts such as common threats, security controls, and risk-related scenarios. We conducted a survey with 199 participants, including 155 undergraduates and 44 graduates, and evaluated their performance based on three levels of exposure to cybersecurity education: no prior exposure (n=36), one source of exposure (n=81), and two or more sources (n=82). The results reveal a significant correlation between exposure to cybersecurity education and improved performance. The mean percentage of correct answers increased from 72.11% for those with no exposure to 79.35% for those with one source and reached 85.07% for those with two or more sources. Furthermore, students consistently underestimated their knowledge on the topic, although this perception gap diminished with increased exposure. These findings highlight the need for incorporating comprehensive cybersecurity into Information Technology (IT) curricula to enhance awareness and reduce risks associated with professional negligence, particularly among future IT practitioners in Brazil.